Standardization and validation of phytometabolites by UHPLC and high‐performance thin layer chromatography for rapid quality assessment of ancient ayurvedic medicine, Mahayograj Guggul. Issue 10 (25th February 2022) - Balkrishna, Acharya; Tomer, Meenu; Joshi, Monali; Gujral, Seema; Kumar Mishra, Rajesh; Srivastava, Jyotish; Varshney, Anurag
Abstract : Mahayograj Guggul is an ancient ayurvedic medicine, prescribed for various joint disorders like arthritis, gout, and rheumatism. The present research was envisaged to develop a simple, sensitive, and comprehensive analytical method for standardization of Mahayograj Guggul. The analysis was conducted for gallic acid, protocatechuic acid, vanillic acid, cinnamic acid, piperine, guggulsterone‐E, and guggulsterone‐Z by high‐performance thin‐layer chromatography, and additionally ferulic acid, ellagic acid, and picroside I by ultra high‐performance liquid chromatography. These developed methods were validated as per international guidelines, and were found linear ( r 2  > 0.99), sensitive, precise (relative standard deviation < 5%), and accurate with recovery values (85–105%). The limit of detection and quantification were in the range of 0.11–23.6 and 0.33–71.51 μg/g. Gas chromatography tandem mass spectrometry was used to develop Mahayograj Guggul fingerprinting profile and to identify mid‐polar or nonpolar compounds. Proximate analysis was used to ascertain the functional groups present in Mahayograj Guggul. Ultra high‐performance liquid chromatography and gas chromatography tandem mass spectrometry were further employed to authenticate quality reproducibility in the active ingredients of Mahayograj Guggul in six commercial batches. Taken together, these analytical methods provide a scientific basis and reference for quality control evaluation of Mahayograj Guggul and similar traditional broad‐spectrum formulations.